Validade relativa de métodos de avaliação do consumo de frutas e hortaliças - Mariana Souza Lopes (2015)
The assessment of the consumption of fruits and vegetables (FH) becomes relevant for their contribution for health protection. However, this assignment is challenging because of the randomness of food consumption and the multiple factors that interfere in its accuracy. OBJECTIVE: To evaluate the relative validity of the methods of consumption of fruits and vegetables in users of the Health Academy Program in Belo Horizonte, Minas Gerais. METHODS: Cross-sectional study with users 20 years old or more of representative sample of the poles of the Health Academy Program in Belo Horizonte / MG. Socioeconomic, anthropometric and FH consumption data were collected from structured and tested questionnaire. The median of consumption was compared in grams of FH (except tubers) tertiles and suitability of these foods second test methods: Brief Assessment of consumption of fruits and vegetables (QBreve-FH) and Food Frequency Questionnaire (QFA- FH), and reference method: 24 hours Food Recall (24HR) associated with the kit of household measures. The correlation coefficient was calculated to Spearman, Kappa and Wilcoxon tests according to age, sex, education level and body mass index. RESULTS: The sample consisted of 299 individuals, 86.6% were female with a median of 57 (interquartile range of 48 to 65) years old. It was observed that the correlation between the test and reference methods varied between poor and moderate. Best correlations are observed for evaluation of fruit second QBreve-FH (r = 0.427), mainly among individuals with higher education (r = 0.521) and overweight (r = 0.551). There were no statistical differences between the consumption in grams of fruit obtained by QBreve-FH and the 24-hour recall, the same comparison resulted in higher percentages of exact classification in tertiles (46.1%). All test methods overestimated intake of vegetables and fruits and vegetables when combined. Poor correlation when the suitability of these foods in grams was analyzed, still showed. CONCLUSÃO: Neither of tested methods are extremely accurate, to evaluate the consumption of fruits, vegetables, and fruits and vegetables combined. However, slightly more significant results were presented by QBreve-FH in the evaluation of fruit consumption, which ensures yours relative validity and use in the investigation of these foods.